The effect of recombinant human fibroblast growth factor‐18 on articular cartilage following single impact load. Issue 7 (9th April 2014) - Barr, Lynne; Getgood, Alan; Guehring, Hans; Rushton, Neil; Henson, Frances M. D.
ABSTRACT The aim of this in vitro study was to ascertain the effect of recombinant human Fibroblast Growth Factor‐18 (rhFGF18) on the repair response of mechanically damaged articular cartilage. Articular cartilage discs were harvested from healthy mature horses (n = 4) and subjected to single impact load (SIL). The impacted explants, together with unimpacted controls were cultured in modified DMEM ± 200 ng/ml rhFGF18 for up to 30 days. Glycosaminoglycan (GAG) release into the media was measured using the dimethylmethylene blue (DMMB) assay. Aggrecan neopepitope CS846, collagen type II synthesis (CPII) and cleavage (C2C) were measured by ELISA. Histological analysis and TUNEL staining were used to assess repair cell number and cell death. Impacted explants treated with rhFGF18 showed significantly more GAG and CS846 release into the media (p < 0.05), there was also a significant decrease in C2C levels at Day 20. Loaded sections treated with rhFGF18 had more repair cells and significantly less cell death (p < 0.001) at Day 30 in culture. In an in vitro damage/repair model, rhFGF18 increases the proteoglycan synthesis, the repair cell number and prevents apoptosis at Day 30. This suggests that rhFGF18 may be a good candidate for enhancement of cartilage repair following mechanical damage. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:923–927, 2014.